2004
DOI: 10.1037/0894-4105.18.2.384
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Functional Hemispheric Asymmetry of Language in Tinnitus Sufferers.

Abstract: The authors tested functional hemispheric asymmetry through word dichotic listening and lateralized lexical decision tasks in tinnitus patients and controls stimulated by a continuous tinnitus-like noise to test the influence of a tinnitus-like external stimulation. A classic right-ear advantage was shown in the auditory task for all but right-ear tinnitus patients, who performed as equally badly when the stimuli were presented to the right and left ears. Concerning the visual task, all participants demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Importantly, this study evidenced impaired speech-in-noise comprehension in the unaffected ear which argues again for impairment with strong contributions from central processes (note that publications studying patients with hearing aids were excluded from this review; this study was included, however, because the unaffected ear was tested). Similarly arguing for an involvement of central processes, Cuny et al (2004) reported left hemispheric dominance (i.e., a right ear advantage) in controls employing a word dichotic listening and lateralized decision task. In contrast, tinnitus patients did not show such a hemispheric asymmetry for language processing.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Importantly, this study evidenced impaired speech-in-noise comprehension in the unaffected ear which argues again for impairment with strong contributions from central processes (note that publications studying patients with hearing aids were excluded from this review; this study was included, however, because the unaffected ear was tested). Similarly arguing for an involvement of central processes, Cuny et al (2004) reported left hemispheric dominance (i.e., a right ear advantage) in controls employing a word dichotic listening and lateralized decision task. In contrast, tinnitus patients did not show such a hemispheric asymmetry for language processing.…”
Section: Resultsmentioning
confidence: 98%
“…Are the impairments in speech processing a direct consequence of attentional impairments or are they both the consequence of underlying common functions? The majority of authors agree that for the development of chronic tinnitus peripheral damage is accompanied by neuroplastic processes of central functions (e.g., Newman et al, 1994; Cuny et al, 2004; Paglialonga et al, 2011; Mertens et al, 2013). If attentional functions and/or working memory and/or language processing are per se affected, then this should become obvious independent from the domain of input.…”
Section: Discussionmentioning
confidence: 99%
“…Cuny et al (2004a) proposed that tinnitus modifies the organization of functions associated with auditory language processes. They concede that an explanation in terms of attention cannot be eliminated.…”
Section: Experimental Investigation Of a Tinnitus áCognition Nexusmentioning
confidence: 99%
“…The hypothesis that there is reorganization of cerebral functions resulting from tinnitus has been considered empirically (Cuny et al, 2004a;Cuny et al, 2004b) and theoretically (Zenner & Zalaman, 2004). Cuny et al (2004a) proposed that tinnitus modifies the organization of functions associated with auditory language processes.…”
Section: Experimental Investigation Of a Tinnitus áCognition Nexusmentioning
confidence: 99%
“…The tinnitus side also affects the correlation between tinnitus pitch and the frequency of maximum hearing loss, i.e., tinnitus pitch and hearing loss frequency are significantly correlated for right sided tinnitus and not for left sided ones (Schecklmann et al, 2012). On the other hand, it has been shown that only right sided tinnitus specifically impairs the classic right-ear advantage in a dichotic auditory listening task (Cuny et al, 2004a). Similarly, even if auditory attention is preferentially focused toward the tinnitus ear in case of unilateral tinnitus, tinnitus patients are better at categorizing a target sound in the right ear and/or to be less distracted by a deviant sound presented in the left ear (Cuny et al, 2004b).…”
Section: Discussionmentioning
confidence: 99%